The Outbreak of COVID-19 and Islamic Stock Market Responses in Indonesia - Rianda Rizky Permata; Budi Purwanto; Wita Juwita Ermawati (The Winners, 2021)
The research intended to analyze the overreaction phenomenon in Islamic stocks due to COVID-19 as well as the influencing factors by utilizing different test methods and cross-sectional regression. The research employed data on the daily stock prices from August 9th, 2019 to October 26th, 2020 on the Jakarta Islamic Index (JII) and the stocks utilized during the period of events. The sample of the research utilized seven events related to COVID-19. The findings reveals that the announcement of COVID-19 transmission and lockdown (Event 2) causes overreaction in winner stocks. Meanwhile, the overreaction phenomenon of loser stock is due to the announcement of the United States fiscal stimulus (Event 5) and the announcement of the PSBB (Event 6). Furthermore, the new normal announcement event (Event 7) triggers overreaction in the winner and loser stocks. The results indicate that Islamic stocks continue to have several transactions which are prohibited by the Fatwa DSN MUI in the short term. In this case, the variables that impact the overreaction phenomenon are shown to be substantially and negatively linked to leverage and market capitalization, while trading volume significantly influences and has a positive correlation with the overreaction phenomenon.